1976
DOI: 10.4269/ajtmh.1976.25.177
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenesis of Vesicular Stomatitis Virus, Serotype Indiana, in Aedes Aegypti Mosquitoes

Abstract: Analysis of infectious virus particles after intrathoracic injection revealed that Aedes aegypti mosquito tissues are capable of supporting the growth of vesicular stomatitis virus (VSV), serotype Indiana. Although all tissues assayed (salivary gland, midgut, diverticulum, malphigian tubules, and ovary) were capable of supporting VSV growth, the salivary gland was the only organ capable of maintaining an appreciable amount of virus for periods longer than 9 days postinfection. Electron microscopic studies of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The transmission cycle of this virus is currently unclear. Seasonal epizootics and isolation of virus from sand¯ies, black¯ies, and mosquitoes have indicated arthropod transmission (Liu & Zee 1976, Francy et al 1988.…”
Section: Introductionmentioning
confidence: 99%
“…The transmission cycle of this virus is currently unclear. Seasonal epizootics and isolation of virus from sand¯ies, black¯ies, and mosquitoes have indicated arthropod transmission (Liu & Zee 1976, Francy et al 1988.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that in nature, VSV exploits both hematophagous and herbivorous vector transmission mechanisms. VSV has been shown to replicate in a variety of hematophagous insects (2,3,9,11,17), as well as in two nonhematophagous insects: leafhoppers (7) and grasshoppers (10). Although most of these insects do not travel distances great enough to explain the typical pattern of VSV spread to new and distant areas during outbreaks, the migratory grasshopper M. sanguinipes is an exception.…”
Section: Discussionmentioning
confidence: 98%
“…aegypti tissues supported the growth of both VSV serotypes after intrathoracic injection [11,80]. The multiplication of Indiana and New Jersey strains showed slightly similar infection patterns reaching the highest viremias between 2 and 3 days after injection and lower peaks after 8 days when the infection was reduced in all organs, but remained high in the salivary glands only for VSV-IN [11,80]. Interestingly, higher doses of virus inoculation caused no increase in mosquito whole body virus titers [80].…”
Section: Vectors and Mechanisms Of Transmissionmentioning
confidence: 99%
“…Information regarding transmission, duration, and geographic spread during epizootics is based largely on case reporting by veterinarians and limited entomological collections conducted during these sporadic outbreaks [4,9]. In addition to direct contact, aerosol, and fomites [1,10], virus transmission routes clearly involve insect vectors, such as mosquitoes [11], sand flies [12], black flies [13,14], and biting midges [15,16]. In terms of virus persistence in nature, serological surveys have shown that in addition to domestic livestock, many species of wild animals develop neutralizing antibodies to the virus [17,18,19,20]; however, a definitive natural host reservoir remains unclear and transmission cycles between vectors and wildlife have not been established [2].…”
Section: Introductionmentioning
confidence: 99%